Indução de calos em anteras e poliploidia em genótipos de melancia - Silva, Carla Maria de Jesus (2018)
The watermelon (Citrullus lanatus) is a very important vegetable for a region of Northeast Brazil due to its adaptation as the natural conditions and the good characteristics of the fruit that are obtained. The aims of the current study are to assess watermelon genotype responses to calluses in anthers by using growth and temperature regulators, and to induce polyploidy through colchicine use (at different concentrations), exposure time, mechanical scarification and application methods. Anthers of Smile and Sugar Baby lines were inoculated in MS medium at different concentrations of 2.4-D or of BAP with 2.4-D, in combination with the pre-treatment (low temperature). Crimson Sweet cultivar seedlings were treated with different colchicine concentrations at two different times, with and without scarification, in order to induce polyploidy. Line LDRO was subjected to different colchicine concentrations at two different times and application methods: a) direct in the seed method (with, and without, scarification) (DSM, WE and WOE), b) Radicle emission method (ERM), c) Hypocotyl and root insertion point method (HRIM), d) At the apex of the seedling method (ASM) and e) Inverted hypocotyl method (IHM). Crimson Sweet flower buds were subjected to colchicine, at two different times, in order to induce polyploidy. Results have shown that 2.4-D often induced callus formation in both lines, but BAP/2.4-D interaction and pre-treatment did not increase the induction frequency. Crimson Sweet showed higher induction rate at 0.2% colchicine for 48h, WE. Line LDRO presented plants with tetraploid cells at 0.2% colchicine for 24 and 48h. The method 0.2% DSM, WE and WOE also generated plants with tetraploid cells. The diameter of treated pollen grains in flower buds have increased; the higher rate of non-reduced gametes induction was 16.07% and flower bud diameter (1.5mm) was estimated as adequate for induction